The relationship between psychological responses and pain levels in post-thyroidectomy patients at dr. Iskak General Hospital, Tulungagung - Dahlia, Dina; Hidayah, Nurul; Ciptaningtyas, Maria Diah; Arif, Taufan; Subekti, Imam (Science Midwifery, 2025)
Background: Patients undergoing thyroidectomy surgery often experience pain and psychological changes such as anxiety, stress, and depression. Objective: This study was conducted to determine the relationship between psychological responses and pain levels in post-thyroidectomy patients at Dr. Iskak Tulungagung Regional General Hospital. Methods: This study used a correlational analytic design with a cross-sectional approach. A sample of 34 patients was selected using a purposive sampling technique. Data were collected through interviews using two main instruments: the Depression Anxiety and Stress Scale (DASS) questionnaire to measure psychological responses and the Neck Pain and Disability Scale (NPADS) to measure pain levels within 24 hours after surgery. Data were analyzed using the Spearman Rank correlation test. Results: The study showed that the majority of patients experienced severe psychological responses (38.2%) and pain ranging from severe to very severe (26.5%). Statistical tests showed a very strong and significant relationship between psychological responses and pain levels (r = 0.959; p = 0.000). Conclusion: This study contributes to strengthening the biopsychosocial approach in perioperative nursing. Practical implications suggest that psychosocial interventions should be integrated into postoperative pain management.